Family Ownership And Growth Opportunity AS Determinant of Firm Value With CSR Disclosure AS An Intervening Variable - Aruning Puspita, Dyah; Eka Sari, Bela Dwi; Sugiono, Djoko (Jurnal Penelitian Ekonomi Dan Akuntansi, 2023)
The study aims to examine the effect family ownership and growth company on firm value by disclosure corporate responsibility as an intermediate variable.. The hypothesis was tasted using PLS-SEM. Family ownership variable are measured by the share of family ownership, the growth company variable is measured by sales growth, the corporate social responsibility disclosure variable measured by CSR disclosure index and the firm value variable is measured by PBV. The result showed that family ownership and growth company has no effect on firm value. CSR disclosure has positive effect on firm value. CSR disclosure is able to intermediate that effect of family ownership in the firm value, while CSR disclosure cannot intermediate the effect of growth company in the firm value.